Acute myeloid leukaemia. Issue 10147 (18th August 2018) - Short, Nicholas J; Rytting, Michael E; Cortes, Jorge E
Summary: For several decades, few substantial therapeutic advances have been made for patients with acute myeloid leukaemia. However, since 2017 unprecedented growth has been seen in the number of drugs available for the treatment of acute myeloid leukaemia, with several new drugs receiving regulatory approval. In addition to advancing our therapeutic armamentarium, an increased understanding of the biology and genomic architecture of acute myeloid leukaemia has led to refined risk assessment of this disease, with consensus risk stratification guidelines now incorporating a growing number of recurrent molecular aberrations that aid in the selection of risk-adapted management strategies. Despite this promising recent progress, the outcomes of patients with acute myeloid leukaemia remain unsatisfactory, with more than half of patients ultimately dying from their disease. Enrolment of patients into clinical trials that evaluate novel drugs and rational combination therapies is imperative to continuing this progress and further improving the outcomes of patients with acute myeloid leukaemia.